Genetic erosion of perennial forage grasses in Morocco: first observations - Shaimi N.; Alfaiz C.; Saidi N. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Morocco has one of the richest flora in the western Mediterranean region due to the diversity of ecological and climatic conditions. This positions Morocco as one of the main centres of diversity for Phalaris, Festuca and Dactylis spp. Unfortunately, this wealth is threatened by several factors, such as drought and intensive grazing pressure. In order to safeguard germplasm ex situ and to evaluate the rate of genetic erosion, two collections of Phalaris aquatica, Festuca arundinacea and Dactylis glomerata were realized in Morocco in 2004 and 2007 within the framework of the PERMED project. A total of 64 accessions from 41 sites were collected from different areas: Middle and High Atlas, Rif mountains and coastal region. Site observation during collection trips has confirmed the scarcity of the target species by comparing the collected information to the previous collection data of 1994. Therefore, further collections should be obtained and actions should be initiated for the in situ conservation of these threatened species.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)